2007
DOI: 10.1111/j.1365-2141.2007.06561.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum free light chain ratio at diagnosis in multiple myeloma

Abstract: Summary The prognostic value of baseline serum free light chain ratio (sFLCR) was investigated in 94 multiple myeloma (MM) patients. sFLCR was calculated as κ/λ or λ/κ, depending on the patients’ dominating monoclonal light chain. Median baseline sFLCR was 3·57 in κ‐MM patients, 45·09 in λ‐MM. ‘High’ sFLCR (≥ the observed median value for κ‐ and λ‐MM respectively) correlated with elevated serum creatinine and lactate dehydrogenase, extensive marrow infiltration and light chain type MM. The 5‐year disease‐speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 12 publications
6
68
1
9
Order By: Relevance
“…9,12,29,32 Kyrtsonis et al 32 found that in 94 MM patients rFLC was prognostic (Figure 3a). Median baseline rFLC was 3.6 in k-MM patients and 0.02 in l-MM.…”
Section: Multiple Myelomamentioning
confidence: 94%
See 1 more Smart Citation
“…9,12,29,32 Kyrtsonis et al 32 found that in 94 MM patients rFLC was prognostic (Figure 3a). Median baseline rFLC was 3.6 in k-MM patients and 0.02 in l-MM.…”
Section: Multiple Myelomamentioning
confidence: 94%
“…'High rFLC' for patients with clonal kappa or lambda disease was 3.6 and 0.02, respectively. (Kyrtsonis MC et al 32 Prognostic value of serum-free light chain ratio at diagnosis in multiple myeloma. Br J Haematol.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…The serum FLC ratio at diagnosis is prognostic in multiple myeloma (Kyrtsonis et al, 2007) and high serum levels of FLC associated with a rapid reduction in response to therapy defines an aggressive myeloma subtype with a poor prognosis (van Rhee et al, 2007). In contrast a retrospective study of patients with intact immunoglobulin myeloma in the UK MRC trials did not show any correlation between FLC levels at diagnosis and survival .…”
Section: Prognostic and Clinical Correlations Of Serum Flc In Multiplmentioning
confidence: 99%
“…Although the SPEP is used for clinical management of these patients, serum FLC measurements also play a valuable role. Serum FLC at diagnosis is felt to be an independent prognostic indicator, with high levels being associated with poorer prognosis, particularly when the levels drop rapidly in response to treatment [11,12]. Serum FLC are also used to monitor for disease progression and response to treatment in nearly all myeloma patients.…”
Section: Clinical Applicationsmentioning
confidence: 99%